The Chinese political novel: migration of a world genre - Yeh, Catherine Vance (Harvard East Asian monographs, 2015)
The formation of a world genre : the political novel -- Forming the core -- Global migration : the Far East -- Bringing the world home : the political novel in China -- The migration of literary forms : transcultural flow and the Japanese model -- "Reform of governance" and the new public sphere -- Women and new China -- In search of new heroes -- Beginning of the beginning : the wedge chapter